Choice, Order Statistics and the Distribution of Earnings - Sattinger, Michael (Journal of Income Distribution®, 1997)
This paper analyzes the distribution of earnings as being generated by workers choosing among occupations on the basis of earnings maximization. A worker’s earnings then have characteristics of an order statistic. The extension to multiple occupations leads to the revision results from A.D. Roy’s two-occupation case. An additional occupation raises expected earnings while in general reducing earnings inequality. Asymptotic results from order statistics suggest that the process of occupational choice determines a limiting distribution of earnings independently of underlying distributions of occupational abilities.